MICROANATOMICAL CHANGES OF PANCREAS WITH EFFECT OF ACUTENS AT ZUSANLI (ST36) ACUPOINTS IN STREPTOZOTOCIN INDUCED DIABETIC RATS: Life Science-Histology - SUBBULAKSHMI; SIVAKUMAR, GIRIJA; NARAYANA MURTHY, SATHIYA (International Journal of Life Science and Pharma Research, 2019)
Acupuncture is an alternative and complementary medicine used throughout the World to treat various chronic disorders including diabetes. The aim of this present study is to explain the hypoglycemic effect of non-invasive stimulation with Acu-TENS at bilateral Zusanli (ST36) acupoints in Streptozotocin(45 mg /kg / body weight / IP) induced diabetic rats. The Acu - TENS therapy was given with low frequency 15 HZ, high intensity and width of 5 sec pulse at the Zusanli(ST36) acupoints in diabetic induced rats for 5 minutes every day without anaesthesia for 60 days. A more steady significant (p ≤ 0.01) decrease in fasting blood glucose level was noted in Zusanli acupoints treated diabetic rats and compared with antidiabetic drug (pioglitazone,7.5 mg / kg /body weight) treated rats.The acupuncture treated diabetic rats showed more significant (p ≤ 0.01) decrease in total cholesterol, triglycerides, low density lipid and significant increase in high density lipid.Histopathological examination of pancreas in Zusanli acupoints treated diabetic rats showed near normal architecture and regular shaped islets with regeneration of cells and compared with anti-diabetic drug treated rats pancreas. Stimulation at ST36 acupoints produced antidiabetic effects and improved lipid metabolism may be due to increase in insulin secretion through the mediation of β- endorphin and stimulation of Qi (energy flow) and utilisation of energy due to mild muscle twitching during stimulation.